Extracranial Vertebral Artery Aneurysm Rupture Complicated by Extrapleural Haematoma. (2018) - Nenadic, D.; Balevic, M.; Milojevic, M.; Tanskovic, S.
Abstract : Introduction: Extracranial vertebral artery aneurysm (EVAA) and extrapleural haematoma (EH) are rare clinical findings most often associated with blunt or penetrating trauma. However, EVAA rupture can be complicated by development of a large EH. Report: A 50 year old man underwent an emergency thrombectomy followed by graft reconstruction of an aorto-bi-femoral bypass. The post-operative course was complicated by respiratory failure and severe anaemia. Computed tomography revealed EVAA rupture and EH, so ligation of EVAA was performed with thoracotomy. Discussion: In a patient with extensive peripheral vascular disease and rapid development of EH, the rupture of a supra-aortic vessel aneurysm might be considered. Highlights: Extracranial vertebral artery aneurysm is a rare clinical finding, representing less than 0.5% of all reported aneurysms. Extrapleural haematoma is a rare complication of vertebral artery aneurysm rupture. Extrapleural haematoma is a diagnostic challenge and can be life threatening.